Causes of Visual Impairment and Blindness in a Clinic Population from Puerto Rico - Rodríguez-Ruiz, Neisha M.; Rivera-Figueroa, Marta N.; Colón-Sanchez, Claudia (Puerto Rico Health Sciences Journal, 2025)
Objective: This study aimed to investigate the leading causes of visual impairment (VI) and blindness in a low vision clinic from Puerto Rico and to assess the distribution of low-vision devices and rehabilitation approaches prescribed to patients. Methods: A retrospective cross-sectional health record study of patients evaluated at the Low Vision Clinic from the Interamerican University of Puerto Rico School of Optometry Eye Institute between 2007 and 2024 was performed. Subjects considered had a comprehensive visual examination followed by a low vision evaluation. Ocular history, causes of visual loss, best-corrected visual acuity, and non- conventional optical devices prescribed were recorded. VI and blindness were classified according to the United States’ definitions. Results: A total of 270 records of subjects older than four years of age were included. The most prevalent causes of VI and blindness were retinal dystrophy (14.8%), diabetic retinopathy (13.7%), and albinism (13.0%). The most common causes of VI by age group were albinism in the pediatric group (42.2%), retinal dystrophy in adults (24.0%), and cataracts (25.8) in the geriatric population. The predominant VI classification was moderate VI for 37.0%. The closed caption television system was the most common low-vision device prescribed to subjects (19.3%). Conclusion: This study provided insights into the causes of VI and blindness in Puerto Rico. These findings underscore the need for targeted interventions and public health initiatives to improve accessibility to visual rehabilitation. Further research is warranted to explore additional factors influencing access to care and evaluate the effectiveness of interventions addressing VI in Puerto Rico.